Study of the underlying event in top quark pair production in pp collisions at 13 TeV; European Physical Journal C; Vol. 79, iss. 2 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Asilar E. Ece; Bergauer T. Thomas; Babaev A. A. Anton Anatoljevich (2019, 2019)
Title screen